2010
DOI: 10.1001/archsurg.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Analysis of Necrotizing Enterocolitis Within 11 958 Neonates Undergoing Cardiac Surgical Procedures

Abstract: Through an analysis of 2 databases, we describe outcomes among 11 958 neonates with congenital heart disease undergoing cardiac procedures, with 194 developing necrotizing enterocolitis (NEC). Neonates with congestive heart failure or those undergoing systemic to pulmonary artery shunting were more likely to develop NEC, but these patients had inpatient mortality similar to that of their non-NEC counterparts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
5
16
1
Order By: Relevance
“…In this study, all NEC events were observed in the SV group, consistent with the findings of previous studies [17, 18]. However, splanchnic rSO 2 showed no corresponding difference between the SV patients with and without NEC before or after initiation of feedings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, all NEC events were observed in the SV group, consistent with the findings of previous studies [17, 18]. However, splanchnic rSO 2 showed no corresponding difference between the SV patients with and without NEC before or after initiation of feedings.…”
Section: Discussionsupporting
confidence: 92%
“…Necrotizing enterocolitis (NEC), a neonatal disease in which the mucosal barrier of the gut is inflamed and breached by pathogenic enteric bacteria, resulting in intestinal injury, is one such morbidity associated with CCHD and CHS [17, 18]. In particular, single-ventricle (SV) heart disease and systemic-to-pulmonary artery shunting are associated with the development of NEC [17, 18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previously conducted retrospective study using the National Inpatient Sample and the Kids’ Inpatient Database, infants with congenital heart disease were evaluated for the development of NEC after undergoing cardiac surgery. 12 The investigators identified infants who developed NEC and who had a coexisting diagnosis of congenital heart disease. Of the 194 patients with congenital heart disease who developed NEC, 57 were diagnosed with secundum ASD, and 61 were diagnosed with a VSD in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that, of all infants who underwent surgery with heart disease and developed NEC, approximately 60% had either an ASD or a VSD. 12 A study of infants with left-to-right intra-cardiac shunt, inclusive of infants with ASD, VSD, atrioventricular septal defect, and persistent ductus arteriosus, demonstrated increased frequency of NEC. 13 In our analysis, we excluded infants with a diagnosis of atrioventricular septal defect and those treated with prostaglandins.…”
Section: Discussionmentioning
confidence: 99%